2010
DOI: 10.1039/c0ay00558d
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of organotin compounds in environmental samples with semi-permanent coated capillaries by capillary electrophoresis coupled with inductively coupled plasma mass spectrometry

Abstract: A novel method using capillary electrophoresis (CE) coupled with inductively coupled plasma mass spectrometry (ICP-MS) for the separation of four organotin compounds has been developed. Semipermanent coating of dioctadecyl dimethyl ammonium chloride (DDAC) was applied and investigated to enhance separation efficiency of trimethyltin (TMT) chloride, tributyltin (TBT) chloride, dibutyltin (DBT) dichloride and monobutyltin (MBT) trichloride. The electrolyte composition and ionic strength were optimized. Running b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…It is required to maintain a stable electrical circuit from CE to nebulizer, introduce CE effluent into ICP-MS efficiently and keep a low dead volume [21,22]. Currently, typical sheath flow-based interfaces are commonly used, which combine a commercial nebulizer and commercially available tee or cross designed fittings to connect the CE capillary, the Pt electrode, the additional sheath flow liquid and the nebulizer of ICP-MS [23][24][25][26]. Generally, a sheath flow liquid (also called makeup solution) is needed in the interface in order to provide closed electrical circuit and increase the total liquid flow to match the nebulizer flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…It is required to maintain a stable electrical circuit from CE to nebulizer, introduce CE effluent into ICP-MS efficiently and keep a low dead volume [21,22]. Currently, typical sheath flow-based interfaces are commonly used, which combine a commercial nebulizer and commercially available tee or cross designed fittings to connect the CE capillary, the Pt electrode, the additional sheath flow liquid and the nebulizer of ICP-MS [23][24][25][26]. Generally, a sheath flow liquid (also called makeup solution) is needed in the interface in order to provide closed electrical circuit and increase the total liquid flow to match the nebulizer flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability and suitability of the method for wine analysis was demonstrated and contamination by butyl-, phenyl-and octyltins was found in the wines analyzed [135]. In a recently published paper Sun et al reported on the use of capillary electrophoresis coupled with ICPMS for the determination of trimethyltin, tributyltin, dibutyltin and monobutyltin in wines [146]. Furthermore, the suitability of SPE and FAAS for Mn partitioning in wines has been demonstrated by Pohl, who found that Mn is predominantly present in the form of cationic species [147].…”
Section: Zn Sn and Mnmentioning
confidence: 96%
“…The diagram of the interface of CE-ICP-MS used in the experiment has been published elsewhere [21]. As previously illuminated, analytical conditions have to be fit for metal complex stability constant determination.…”
Section: Experimental Optimizationmentioning
confidence: 99%
“…The schematic diagram for the instrument of CE-ICP-MS system has been published elsewhere [10,19,21]. In brief, the separations of the ACE and NECEEM methods were operated on HP 3D CE system (Agilent, Germany).…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation